A Comprehensive Review and Analytical Comparison of Non-Isolated DC-DC Converters for Fuel Cell Applications - Furqan A. Abbas; Thealfaqar A. Abdul-Jabbar; Adel A. Obed; Anton Kersten; Manuel Kuder; Thomas Weyh (Energies, 2023)
The use of renewable energy sources such as solar photovoltaic, wind, and fuel cells is becoming increasingly prevalent due to a combination of environmental concerns and technological advancements, as well as decreasing production costs. Power electronics DC-DC converters play a key role in various applications, including hybrid energy systems, hybrid vehicles, aerospace, satellite systems, and portable electronic devices. These converters are used to convert power from renewable sources to meet the demands of the load, improving the dynamic and steady-state performance of green generation systems. This study presents a comparison of the most commonly used non-isolated DC-DC converters for fuel cell applications. The important factors considered in the comparison include voltage gain ratio, voltage switch stress, voltage ripple, efficiency, cost, and ease of implementation. Based on the comparison results, the converters have been grouped according to voltage level applications, with low voltage applications being best served by converters such as DBC, DuBC, TLBC, 2-IBC, 1st M-IBC, PSOL, SEPIC, and 1st M-SEPIC owing to their lower cost, smaller size, and reduced switch stress. Medium voltage applications are best suited to converters such as TBC, 1st M-TLBC, 2nd M-TLBC, 4-IBC, 1st M-IBC, 2nd M-IBC, 1st M-PSOL, 2nd M-PSOL, 1st M-SEPIC, and 2nd M-SEPIC, which offer higher efficiency. Finally, high voltage applications are best served by converters such as TBC, 1st M-TBC, 2nd M-IBC, 3rd M-IBC, 3rd M-PSOL, 4th M-PSOL, 2nd M-SEPIC, 3rd M-SEPIC, and 4th M-SEPIC.